Legal Review of Producers' Liability for Trademarks Incompatible with Product Advertisements in the Perspective of Consumer Protection Law - Arifin, Alfredo Juniotama; Aulia, Riska; April, Jerica; Saly, Jeane Neltje (CV. Rayyan Dwi Bharata, 2023)
People's lives in the digitalization era are heavily influenced by online activities. This online activity reflects cultural changes and digital transformation that is happening in society. The internet has become an integral part of everyday life, facilitating convenience, global connectedness and greater accessibility in various aspects of our lives. Advances in technology and the development of the internet have changed the way we interact, work, shop, communicate and access information. Online shopping has become very popular in recent years. Consumers only need to use gadgets to find the items they need, therefore it is not uncommon for manufacturers to create attractive advertisements to market their products in e-commerce. However, behind these attractive advertisements, there are not a few manufacturers who advertise their products excessively and do not match the trademarks they market, so that consumers are deceived by these attractive advertisements. This research involves collecting data through searching and analyzing literature such as journal articles, books and other resources relevant to the research topic through academic databases and digital libraries. The results of the study show that business actors must be responsible for the advertisements they create if they are not in accordance with the trademarks they market.